1997
DOI: 10.1016/s0893-133x(97)00033-x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A Agonists: A Potential New Type of Atypical Antipsychotic

Abstract: The systemic intraperitoneal (i.p.) The systemic administration of adenosine agonists in rodents has been shown to induce a pronounced dosedependent depression of spontaneous motor activity (Vapaatalo et al. 1975;Snyder et al. 1981;Durcan and Morgan 1989;Heffner et al. 1989;Nikodijevic et al. 1991;Jacobson et al. 1993;Ferre et al. 1994a). This behavioral effect is most probably mediated at the central level, since it is also induced after their intraventricular or intracerebral administration (Barraco et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 50 publications
8
88
0
1
Order By: Relevance
“…The dose range of CGS-21680 used also reduces alcohol drinking in mice (Nam et al, 2013), implying a relationship between circadian rhythm improvement and decreased drinking. Similar to several studies (Houchi et al, 2013;Jones et al, 2012;Knapp et al, 2001;Rimondini et al 1997), we observed that CGS-21680 reduced locomotor activity. Alpha (active-phase duration) was reduced in CGS-21680-treated mice of both genotypes vs vehicle-treated WT controls (Figure 4d).…”
Section: Discussionsupporting
confidence: 91%
“…The dose range of CGS-21680 used also reduces alcohol drinking in mice (Nam et al, 2013), implying a relationship between circadian rhythm improvement and decreased drinking. Similar to several studies (Houchi et al, 2013;Jones et al, 2012;Knapp et al, 2001;Rimondini et al 1997), we observed that CGS-21680 reduced locomotor activity. Alpha (active-phase duration) was reduced in CGS-21680-treated mice of both genotypes vs vehicle-treated WT controls (Figure 4d).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with these previous findings of an interaction between DA and adenosine receptors, adenosine A 2A agonists have been shown to induce effects that resemble those produced by DA antagonists or DA depletions (Heffner et al 1989;Barraco et al 1993;Ferré 1997;Rimondini et al 1997). Administration of the adenosine A 2A receptor agonist CGS 21680 into the ventricles inhibited acquisition and expression of wheel running behavior (Cabeza de Vaca et al 2007).…”
Section: Introductionsupporting
confidence: 84%
“…Similarly, using BRET methodology, cocaine was shown, through direct actions on D2R, to induce a conformational change in the A2-D2 complex, resulting in reduced BRETmax, potentially indicative of a reduction in heteromer expression . In schizophrenia animal models, evidence of antipsychotic effects of the A2 receptor (A2R) agonist CGS 21680 have been demonstrated (Andersen et al, 2002;Rimondini et al, 1997), and adenosine augmentation has been shown to ameliorate both psychotic and cognitive schizophrenia-like symptoms in mice , potentially by acting at the A2R within the A2-D2 heteromer, and thus reducing the proportion of D2R in the agonist-induced high-affinity state and D2R signaling Fuxe et al, 2010). It has been further suggested that an imbalance in adenosine signaling, a neurotransmitter which modulates both dopamine and glutamate transmission, may be a central factor in the susceptibility to develop schizophrenia (Boison et al, 2012).…”
Section: Adenosine-dopamine Receptor Heteromers: A1-d1 A2-d2mentioning
confidence: 99%